Mutation in Rice Abscisic Acid2 Results in Cell Death, Enhanced Disease-Resistance, Altered Seed Dormancy and Development - Liao, Yongxiang; Bai, Que; Xu, Peizhou; Wu, Tingkai; Guo, Daiming; Peng, Yongbin; Zhang, Hongyu; Deng, Xiaoshu; Chen, Xiaoqiong; Luo, Ming; Ali, Asif; Wang, Wenming; et al. (Frontiers in Plant Science, 2018)
Lesion mimic mutants display spontaneous cell death, and thus are valuable for understanding the molecular mechanism of cell death and disease-resistance. Although a lot of such mutants have been characterized in rice, the relationship between lesion formation and abscisic acid (ABA) synthesis pathway is not reported. In the present study, we identified a rice mutant, lesion mimic mutant9150 (lmm9150), exhibiting spontaneous cell death, pre-harvest sprouting, enhanced growth and resistance to rice bacterial and blast diseases. Cell death in the mutant was accompanied with excessive accumulation of H2O2. Enhanced disease-resistance was associated with cell death and up-regulation of defense-related genes. Map-based cloning identified a G-to-A point mutation resulting in a D-to-N substitution at the amino acid position 110 of OsABA2 (LOC_Os03g59610) in lmm9150. Knock-out of OsABA2 through CRISPR/Cas9 led to phenotypes similar to those of lmm9150. Consistent with the function of OsABA2 in ABA biosynthesis, ABA level in the lmm9150 mutant was significantly reduced. Moreover, exogenous application of ABA could rescue all the mutant phenotypes of lmm9150. Taken together, our data linked ABA deficiency to cell death and provided insight into the role of ABA in rice disease-resistance.